2009
DOI: 10.1088/0031-9155/54/13/006
|View full text |Cite
|
Sign up to set email alerts
|

Generalized model of the microwave auditory effect

Abstract: A generalized theoretical model for evaluating the amplitudes of the sound waves generated in a spherical head model, which is irradiated by microwave pulses, is developed. The thermoelastic equation of motion is solved for a spherically symmetric heating pattern of arbitrary form. For previously treated heating patterns that are peaked at the sphere centre, the results reduce to those presented before. The generalized model is applied to the case in which the microwave absorption is concentrated near the sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the case of the homogeneous spherical head model, for which analytical solutions have been derived [Lin, 1977a,b; Yitzhak et al, 2009] it was found that the pulse width dependence of the induced pressure amplitude at a given location in the head, and at an acoustic angular frequency ω m is of the form P(τ)=Asinωnormalmτ2 here, τ is the pulse width and the amplitude factor A is independent of the pulse width. We have found that this dependence on the pulse width holds to a good approximation even for the complicated biological models treated here.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of the homogeneous spherical head model, for which analytical solutions have been derived [Lin, 1977a,b; Yitzhak et al, 2009] it was found that the pulse width dependence of the induced pressure amplitude at a given location in the head, and at an acoustic angular frequency ω m is of the form P(τ)=Asinωnormalmτ2 here, τ is the pulse width and the amplitude factor A is independent of the pulse width. We have found that this dependence on the pulse width holds to a good approximation even for the complicated biological models treated here.…”
Section: Resultsmentioning
confidence: 99%
“…This is not appropriate for the bottom layer of the head model, so in this case, an absorbing perfectly matched layer (PML; with a 10 cell thickness) was added [Chew and Liu, ]. We verified the accuracy of the elastic FDTD algorithm by applying it to the homogeneous sphere case, for which analytic solutions are available for comparison [Yitzhak et al, ].…”
Section: Fdtd Methods Of Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…One of such manifestations is given by the microwave auditory effect or Allan Frey hearing effect [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], an auditory perception of microwave pulses by humans and animals, which earlier has been considered mysterious. Now, the mystery of this effect is completely resolved within a thermoelastic theory [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] of acoustic wave production in closed resonators (e.g., human or animal head) filled with microwave absorbing tissues having a very large water content (think about heating of food in microwave oven, to realize a possible physical reason). Good reviews are available [ 13 , 14 , 15 ] and the theory and experiment agree convincingly well.…”
Section: Introductionmentioning
confidence: 99%